Cytoskeletal-inhibiting drugs and low levels of Ca2+induce subcellular alterations in Lamiaceae glandular trichomes - Tozin, Luiz Ricardo dos Santos [UNESP]; Machado, Silvia Rodrigues [UNESP]; Boaro, Carmen Silvia Fernandes [UNESP]; Rodrigues, Tatiane Maria [UNESP] (Elsevier, 2021)
Subcellular features of glandular trichomes have been extensively studied in plants of a variety of families, but the role that the cytoskeleton plays in gland morphology and functioning has been neglected. We investigated morphological and subcellular alterations in glandular trichomes of two species of Lamiaceae submitted to cytoskeletal polymerization-inhibiting drugs and low levels of Ca2+, a known modulator of cytoskeleton activity. Plants of Hyptis villosa and Ocimum gratissimum were submitted to Oryzalin and Cytochalasin D and 240 mgL−1, 160 mgL−1, 80 mgL−1, 40 mgL−1 and 0 mgL−1 of Ca2+. Samples were analyzed using scanning and transmission electron microscopy. Both cytoskeleton destabilizing drugs and low levels of Ca2+ led to morphological alterations of the wall structure of glandular head cells in both species, in addition to cytoplasm and organelle degradation. The results showed that cytoskeletal polymerization-inhibiting drugs and low levels of Ca2+ cause similar structural alterations in glandular trichomes which can lead to problems mainly concerning secretion release. New studies involving molecular approaches must be conducted to elucidate the role of cytoskeletal elements during the morphogenesis and functioning of glandular trichomes.
Keywords: Actin filaments; Calcium; Hyptis; Microtubules; Ocimum; Ultrastructure